Amendment additions and their potential effect on soil geotechnical properties: A perspective review. Issue 6 (19th March 2021) - Liu, Fuming; Yi, Shuping; Zhou, Wan-Huan; Chen, Yong-Zhan; Wong, Ming Hung
Abstract: Various remediation technologies have been developed over the past few decades for the remediation of contaminated soils and groundwater. In this paper, little effort is devoted to summarizing and commenting on the recent research on the remediation of contaminated sites. Instead, this paper seeks to present a perspective review of remediation technologies and amendment additions (reagents for site remediation) and their potential effects on geotechnical properties, with a focus on soil strength. The intrusion of highly reactive amendment additions generally turns the soil of a contamination plume from inert to physiochemically active, which brings about changes in the soil's physicochemical properties and subsequently leads to variation in soil strength. This may impact the serviceability and reliability of construction projects. However, few studies shed light on the geotechnical properties of contaminated soil before and after remediation. Attention is drawn to the necessity of incorporating the analysis of geoenvironmental risk in the application of remediation technologies for the sustainable development of land resources. More studies should be carried out to investigate the effects of remediation technologies on the physicochemical and geoenvironmental behavior of contaminated soil. The physicochemical reaction in the pore fluid and the transformation of by-products after remediation associated with geotechnical properties should be further investigated.